Pengaruh Beban Administrasi Kurikulum Merdeka, Tekanan Waktu, dan Dukungan Organisasi terhadap Kesejahteraan Mental Guru SMK di Semarang - Saepurrohman, Andika; Pitaloka, Lola Kurnia (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2025)
This study aims to analyze the effect of administrative workload under the Merdeka Curriculum, time pressure, and organizational support on the mental well-being of vocational high school (SMK) teachers in the business and management department in Semarang City. The research employs a quantitative approach with an explanatory design and survey method. The sample consists of 123 teachers selected through proportional random sampling. Data were collected using a five-point Likert scale questionnaire and analyzed using multiple linear regression with IBM SPSS 22. The findings indicate that administrative workload and time pressure have a significant negative effect on teachers' mental well-being, whereas organizational support has a significant positive effect. The R² value of 42.7% suggests that the independent variables explain a substantial portion of teachers' mental well-being, while the remaining variance is influenced by other factors. These results highlight the importance of reducing administrative workload, managing time pressure, and strengthening organizational support to enhance teachers' mental well-being.